Nitrogen, Phosphorus, and Potassium Requirements to Improve Portulaca oleracea L. Growth, Nutrient and Water Use Efficiency in Hydroponics - Chrysargyris, Antonios; Tzortzakis, Nikos G. (My University, 2025)
Purslane (Portulaca oleracea L.) is an herbaceous species that is traditionally consumed across the world due to its nutraceutical quality, boasting anticancer, anti-inflammatory and antidiabetic properties. These traits render purslane an attractive wild edible species for research and commercial exploitation. The current study examined the effect of different nitrogen (N) concentrations (100–200 mg L−1; as N100, N200) in combination with different levels (decreased 0.66-fold: dec, recommended 1-fold: rec, or increased 1.5-fold: inc) of phosphorus (P; 47–70–105 mg L−1) and potassium (K; 250–350–525 mg L−1) in the nutrient solution (NS) used in hydroponic nutrient film technique (NFT) cultivation. The N200_PKinc NS resulted in improved crop growth compared to N200_PKrec NS, suggesting a positive correlation between optimal N levels (i.e., 200 mg L−1) and increased P and K levels (105 and 525 mg L−1, respectively). Plants grown in N200_PKinc revealed decreased antioxidant activity (e.g., DPPH, FRAP, and ABTS), phenols and flavonoids, while simultaneously increased total soluble solids levels. The recommended levels of P and K mirrored low levels in lipid peroxidation, mainly due to the increase in catalase enzymatic activity. Higher nutrient use efficiency was observed when both N100_PKinc and N200_PKinc were applied, resulting in higher yield and enhanced plant growth, while N100_PKinc produced plants with increased antioxidant activity. These findings suggest that both (N200_PKinc and N100_PKinc) NS have potential benefits for the hydroponic cultivation of purslane, with the latter NS offering additional advantages in terms of higher produce quality.
Keywords: antioxidants; macronutrients; mineral fertilizer; purslane; soilless culture